2022
DOI: 10.7189/jogh.12.04036
|View full text |Cite
|
Sign up to set email alerts
|

Success and time implications of SpO2 measurement through pulse oximetry among hospitalised children in rural Bangladesh: Variability by various device-, provider- and patient-related factors

Abstract: Background Hypoxaemia is one of the strongest predictors of mortality among children with pneumonia. It can be identified through pulse oximetry instantaneously, which is a non-invasive procedure but can be influenced by factors related to the specific measuring device, health provider and patient. Following WHO's global recommendation in 2014, Bangladesh decided to introduce pulse oximetry in paediatric outpatient services, ie, the Integrated Management of Childhood Illness (IMCI) services in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…An observational study from Bangladesh found that after a brief training, health care personnel can obtain a successful pulse oximetry measurement in 60 seconds in children aged <5 years 62 . Razzak et al 63 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An observational study from Bangladesh found that after a brief training, health care personnel can obtain a successful pulse oximetry measurement in 60 seconds in children aged <5 years 62 . Razzak et al 63 .…”
Section: Discussionmentioning
confidence: 99%
“…An observational study from Bangladesh found that after a brief training, health care personnel can obtain a successful pulse oximetry measurement in 60 seconds in children aged <5 years. 62 Razzak et al 63 predicted that implementing a complete trauma system in LMICs could save more than 200,000 lives annually. A systematic review of 2174 articles by Sessions et al 64 evaluated the impact of continuous positive airway pressure on mortality and adverse effects among pediatric patients with respiratory distress and found 20 studies of variable evidence.…”
Section: Dhrmentioning
confidence: 99%
“…To remove these unwanted Using the RGB signals and the transformed YCrCgCb and HSV signals, a dataset of size N × 10 was generated, where N represents the number of frames in the video. In this paper, considering that it takes a minimum of 30 s to successfully measure oxygen saturation [23], signals from 10, 20, and 30 s were used, resulting in dataset lengths of 300, 600, and 900, respectively.…”
Section: Data Preprocessingmentioning
confidence: 99%